Teaching Mission and Pedagogy at African Universities - Andoh, Harris (International Higher Education, 2020)
The theoretical concepts and applied methodology of teaching academic subjects are central to the teaching mission of African universities. However, it is an area that African universities have only brushed over in their structural and directional plans. This article evaluates the first mission of African universities, teaching, and the state of pedagogical training among African scholars. It further enquires whether current programs and efforts are enough to solve the problems associated with teaching and learning.